Mga kagamitang panturo sa paglinang ng mga kakayahan tungo sa mapanuring pagbasa para sa ikatlong taon ng mataas na paaralan - Bautista, Florencia (Bautista) 1923- (s.n.], 1972)
This paper presented a discussion on the different kinds of instructional materials which a teacher may avail herself of in developing skills in critical reading such as giving the connotational meaning of words, inferring on what the author wishes to convey through the use of dictation, distinguishing the facts from opinion, giving a critical evaluation of an editorial, advertisement, or announcement, news report, storyline, poem and the like, constructing a syllogism, conceptualizing, and choosing sentences or paragraphs irrelevant to the main idea of a reading material. Appended to this paper is an example of a lesson plan in developing critical reading skills which the writer made use of in her demonstration teaching.